Strategies for Including the Excluded in Education: A Case of Children with Intellectual Disabilities - Niure, Dhruba Prasad; Shrestha, Madhav Kumar (Education Quarterly, 2023)
This article has been prepared to disclose a number of strategies that need to be implemented to ensure the inclusion of students with intellectual disabilities in education. This research is guided by interpretive paradigm accompanied by institutional ethnography. Eight special education teachers, four resource classroom teachers, and five experts working in the field of inclusive education were chosen as the sample of the study by employing purposive sampling technique. In-depth interview and desk review were used as the main techniques to collect information and then the information were transcribed, edited, classified, and thematized by considering the objective of this study. External audit, peer review and thick description have been used as major techniques to maximize the credibility and authenticity of this article. Results of this study reveal that almost all students with intellectual disabilities were receiving educational services in segregated settings though there are policy provisions of providing inclusive education. Therefore, different strategies such as providing multi-tiered supports, developing sense of belongingness, educating in the mainstream classroom, mobilizing peers, formulating alternative learning standards, creating cooperative learning environment, etc. should be employed to optimize the inclusion of these children in education.